Structural, Optical Properties, and Biodegradation of Potato Starch-Based Bioplastics - Samira Belahcene; Zeid Alia; Abdelouahab Gahtar; Roumaissa Ahmed Salah; El Amine Khechekhouche; Mohammed Messaoudi; Nezar Cherrada; Djilani Ghemam Amara; Ayomide Victor Atoki (Journal of Natural Fibers)
This study compares neutral, alkaline, and acidic treatments for potato starch-based bioplastics, analyzing their structural, optical, and biological properties. Bioplastics Bio(H2O), Bio(NaOH), and Bio(HCL) exhibited densities of 1.38 g/cm3, 1.61 g/cm3, and 1.40 g/cm3, respectively. FTIR analysis revealed glycerol–starch interactions, while XRD confirmed an orthorhombic crystal structure with strong orientation along (211) and (400) planes. Crystallite size, micro-stress, and dislocation density in the (211) plane were 15.399, 0.122, and 0.341 lines/nm2, respectively. Optical analysis showed a direct bandgap in the 250–400 nm range. Biologically, bacteria effectively degraded starch-based plastics, with a white circular colony identified as the most efficient. A pure culture of bioplastic-degrading bacteria was isolated using the streak plate method. These bacteria achieved complete degradation in 48 h in liquid media and 1 month in solid media, validating the study’s reliability and thoroughness.